Related Factors with Type 2 Diabetes Mellitus in Sumatera Island - Adelia Debora Siagian; Rd. Halim; Adelina Fitri (International Journal of Health Engineering and Technology, 2025)
Type 2 Diabetes Mellitus (DM) is one of the disease No infectious with continuing prevalence​ increasing in Indonesia, including in the Sumatra region. Identification factor risk in a way accuracy is very important For support effort prevention and control disease This .This study aiming For analyze connection between a number of factor risks , such as age , type gender , hypertension , and smoking , with incidence of type 2 diabetes mellitus in the population aged ≥15 years in Sumatra Island based on data from the 2023 Indonesian Health Survey (SKI) . This study use design cut cross -sectional with secondary data analysis from SKI 2023. Population study covering 198,687 respondents age ≥15 years in the Sumatra region. Data analysis was carried out in a way univariate and bivariate using the chi-square test and Prevalence Odds Ratio (POR) calculation with 95% confidence interval. Prevalence of type 2 DM in the population studies by 1.8%. Age ≥45 years proven as related factors​ with to the occurrence of DM is age (POR = 14.5; 95% CI: 12.6–16.7), hypertension (POR = 9.2; 95% CI: 8.2–10.3). Gender . ( POR = 1.5 ; 95% CI: 1.4–1.6) Smoking status show connection negative with incidence of DM (POR = 0.7; 95% CI: 0.6–0.8), although allegedly strong influenced by factors confounding. Age factor, hypertension, and types sex is a related factor with The incidence of type 2 diabetes mellitus in the Sumatra region. Findings This confirm importance improvement screening , education style life healthy , and intervention group oriented​ risk tall in effort DM control in Indonesia